Research Difficulties and Possible Green Technology Uses in Cloud Computing (International Journal of Innovative Research in Engineering & Management, 2023)
Clouds technology has sparked a great  deal of curiosity and competition in the information  technology business. As a scaled service distribution  platform in the domain of applications computing, it has  achieved widespread use. Its technical foundations  comprise service-oriented architectures and virtualisation  of software and hardware, among other things. The idea is  for internet platform users to share their capabilities, cloud  collaborators, and cloud providers to create a more  efficient source restraint in the clouds. The technologies is  confronted with a number of significant challenges, and  the current research focuses on the technical problems that  arise during the development and delivery of clouds, as  well as the ramifications of these concerns for  organizations and customers. Cloud computing initiatives  are organized according to their technical aspects, and we  cover related technologies; breakthroughs in the  introduction of procedures, interactions, and norms;  methodologies for modeling and establishing clouds; and  viability, experimenting, and the prospective that is arising  from cloud computing. Clouds technology is a significant  step forward in the direction of green computing, which is  an environmentally viable eternal computing with a very  promising future.
Keywords: Architecture; Cloud Computing; Internet; Models; Software